Application of Croft's 2D geometric aspect model to Sinitic : Mandarin, Cantonese, and Hokkien - Tan, Lye Huat (2018)
This paper introduces Croft's (2012, 2017) two-dimensional geometric aspect model, and applies it to Mandarin, Cantonese and Hokkien discourse data. Building upon his background in cognitive semantics, Croft delineates aspectual structure via two dimensions—the qualitative state dimension, and the time dimension—thereby integrating two parallel, and otherwise non-intersecting, approaches into a single model. This allows him to expand on the Vendlerian situation-type framework substantially, while also illustrating the relationships between various aspectual types. In the light of these considerations, this study is conducted in the hope that Croft's model can adequately account for some of the aspectual phenomena observed in Sinitic, which have proved to be rather problematic for many other analyses. By analyzing discourse data at two different levels (verb-focused vs. particle-focused) this paper aims to see whether the Croftian approach is able to adequately account for at least some parts of Sinitic aspect.